‘We're still here!’ Post-polio syndrome and web activism - Testa, Daniela Edelvis (Universidad Nacional del Litoral, 2018)
The article explores tensions and controversies that emerge around the recognition of a “new” ailment named Post-polio Syndrome (PPS), with the purpose of problematize and discuss the disease and the constituent material of life as essential instruments to discuss the social and economic inclusion boundaries. The mentioned syndrome is a set of unspecified symptoms that can affect those who have had poliomyelitis before, and as a consequence of that, they carry with physical deficiencies for decades. Given the special relevancy that acquires digital communication technologies for people with severe difficulties in their mobility, we need to emphasize a perspective where people with SPP can rely in the collective actions that Polio and PPS support networks have on the Internet, to channel their demands and necessities. The ideas, requirements and resistance that are shown on these sites demonstrate that the internet is an excellent way to let the voice of polio and PPS patients is heard, so that it would be included with a higher workload in social sciences courses as in sanitary courses.